Development of functional cookies with wheat flour, banana flour (Musa paradisiaca), sesame seeds (Sesamum indicum) and storage stability (Scientia Agropecuaria, 2017)
Functional cookies were developed using banana flour (BF) and sesame seeds (SS). Protein, moisture and ash were determined, and farinographic analyzes of flours were performed. The attributes odor, color, flavor, crunch and the IC50 value of the cookies were determined. The results were evaluated with the Complete Randomized Design and the Tukey and Kruskall Wallis test. The flour mixture presented higher protein (10.2%), humidity (14.40%) than BF, but lower than wheat flour. Cookies with 10%, 15% and 20% BF and 8% sesame seeds were selected. Flours with 10%, 15% and 20% BF had similar values of water absorption (≤ 60%) and different values statistically (p ≤ 0.05) for development time, mass stability and degree of softening. Cookies with 20% BF and 8% SS (SC) had IC50 = 17.52 ± 0.25 mg / mL, with moisture, protein, fat, crude fiber, ash and carbohydrates of 1.88%, 10.65%, 22.01%, 1.01%, 1.54% and 62.91%, respectively. SC did not present sensorial statistical differences (p ≤ 0.05) the first two months, the third month decreased the acceptability of the crunch and flavor. In ninety days of storage the IC50 value (29.07 ± 0.92 mg / mL), reducing sugars (1.20 ± 0.02) and pH (5.24 ± 0.01) decreased and humidity (3.83 ± 0.03) increased.